2012
DOI: 10.1038/ijo.2012.118
|View full text |Cite
|
Sign up to set email alerts
|

Severe obesity increases adipose tissue expression of interleukin-33 and its receptor ST2, both predominantly detectable in endothelial cells of human adipose tissue

Abstract: Expression of IL-33 and its receptor ST2 in human adipose tissue is predominantly detectable in endothelial cells and increased by severe obesity indicating an autocrine action. Thus, the adipose tissue microvasculature could participate in obesity-associated inflammation and related complications via IL-33/ST2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
118
4
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(137 citation statements)
references
References 40 publications
9
118
4
6
Order By: Relevance
“…Some macrophages respond to . Taken together, IL-33 may directly activate AAM.It has been reported that IL-33 is produced in the adipose tissue [28,29]. In our study, however, we failed to clearly detect il33 expression in GAT from untreated normal mice (Fig.…”
contrasting
confidence: 53%
“…Some macrophages respond to . Taken together, IL-33 may directly activate AAM.It has been reported that IL-33 is produced in the adipose tissue [28,29]. In our study, however, we failed to clearly detect il33 expression in GAT from untreated normal mice (Fig.…”
contrasting
confidence: 53%
“…On one hand, IL-33 has been considered to prevent adipose tissue inflammation and thus reduce metabolic complications (38,41). However, other studies have linked increased Il-33 levels to morbid obesity and the development of diabetes (40,41). Since IL-33 has been mainly implicated in immune cell function, our findings might provide a link between inflammation and adipocyte differentiation.…”
Section: Discussionmentioning
confidence: 47%
“…Conflicting data exist with regard to the role of the IL-33/Il1rl1/ ST2 axis in metabolism. On one hand, IL-33 has been considered to prevent adipose tissue inflammation and thus reduce metabolic complications (38,41). However, other studies have linked increased Il-33 levels to morbid obesity and the development of diabetes (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…IL-33, discovered in 2005 and widely expressed in fibroblasts, epithelial cells and endothelial cells (16), is reported to exert cardioprotective effects (17,18). In fat tissues, IL-33 and ST2 present a paracrine and positive-feedback signaling mechanism (19,20). Further study shows that the IL-33/ST2 pathway enhances the secretion of T-helper 2 (Th2) cytokines of adipocytes, promotes accumulation of Th2 cells in fat tissues and transforms macrophages into a protective M2 type, all presenting anti-inflammation effects, concomitant with reducing fasting blood glucose and improving insulin resistance (8).…”
Section: Discussionmentioning
confidence: 99%